Notch Signaling in Drosophila Tumor Models. - Djiane, A. (Advances in Experimental Medicine and Biology, 2025)
The Notch pathway represents a juxtacrine signaling pathway, where ligands expressed at the surface of a cell instruct the neighboring cell through the activation of the transmembrane receptor Notch. The Notch pathway controls a wide variety of developmental cell fate decisions and tissue patterning, as well as the biology and differentiation programs of different stem-cell lineages. First described in Drosophila, the Notch pathway is highly conserved throughout evolution, and Notch mutations or Notch pathway alterations have been implicated in an ever-growing set of pathologies, including many cancers where it can act as an oncogene or a tumor-suppressor depending on cancer type and context. Similarly, in Drosophila tumor models, the Notch pathway can either promote or prevent proliferation and tumoral cell behaviors. In this chapter, I will first describe the Notch pathway and its many nodes of regulation, representing as many potential routes to unleash Notch-driven cancers. Then I will review the implication of the Notch pathway and its misregulations in the main larval (imaginal discs, brain) and adult Drosophila tumor models, either as a primary driver or as a contributing factor to tumor development and evolution.